Comparison of Isomerase and Weimberg Pathway for γ-PGA Production From Xylose by Engineered Bacillus subtilis - Halmschlag, Birthe; Hoffmann, Kyra; Hanke, René; Putri, Sastia P.; Fukusaki, Eiichiro; Büchs, Jochen; Blank, Lars M. (Frontiers in Bioengineering and Biotechnology, 2020)
The production of poly-γ-glutamic acid (γ-PGA), a biopolymer consisting of D-and L-glutamic acid monomers, currently relies on L-glutamate or citrate as carbon substrates. Here we aimed at using plant biomass-derived substrates like xylose. γ-PGA producing microorganisms including Bacillus subtilis natively metabolize xylose via the isomerase pathway. The Weimberg pathway, a xylose utilization pathway first described for Caulobacter crescentus, offers a carbon-efficient alternative converting xylose to 2-oxoglutarate without carbon loss. We engineered a recombinant B. subtilis strain that was able to grow on xylose with a growth rate of 0.43 h -1 using a recombinant Weimberg pathway. Although ion-pair reversed-phase LC/MS/MS metabolome analysis revealed lower concentrations of γ-PGA precursors such as 2-oxoglutarate, the γ-PGA titer was increased 6-fold compared to the isomerase strain. Further metabolome analysis indicates a metabolic bottleneck in the phosphoenolpyruvate-pyruvate-oxaloacetate node causing bi-phasic (diauxic) growth of the recombinant Weimberg strain. Flux balance analysis of the γ-PGA producing B. subtilis indicated that a maximal theoretical γ-PGA yield is achieved on D-xylose/D-glucose mixtures. The results of the B. subtilis strain harbouring the Weimberg pathway on such D-xylose/D-glucose mixtures demonstrate indeed resource efficient, high yield γ-PGA production from biomass-derived substrates.